METHODS OF REINNERVATION AFTER AMPUTATIONS IN PATIENTS WITH THE CONSEQUENCES OF COMBAT INJURIES (LITERATURE REVIEW) - Burianov, Olexandr; Smyk, Oleh; Salenko, Maryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
The full-scale aggression of the Russian Federation against Ukraine has significantly increased the number of cases and the structure of factors leading to the performance of such surgical interventions as amputation. There are no reliable statistics on the number of limb amputations performed since the beginning of the full-scale invasion of the Russian Federation into the territory of Ukraine due to objective factors, however, according to preliminary estimates, their number exceeds 50 thousand people. One of the significant problems after limb amputations is pain syndrome, which is observed in 60 to 86 % of patients, which is divided into two types: residual limb pain (RLP) and phantom limb pain (PLP). This problem is relevant for modern world orthopedics and traumatology, the solution of which requires a multidisciplinary approach, and further study will allow to improve treatment tactics and improve the final results. The purpose was to determine the optimal surgical technologies for performing amputations in victims with combat injuries and analyze modern reinnervation methods by studying literary sources. Methods. An assessment of modern publications, systematic reviews, and current recommendations published recently was conducted, which are devoted to methods of treatment and prevention of neuroma formation in limb amputations. A search was conducted in the PubMed, Scopus, Web of Science, and Google Scholar, databases using the following terms: «amputation», «RPNI», «VDMT», «TMR», «phantom», «clinical effectiveness», «post-amputation pain», «BNA», «ANA», «RLP», «PLP», «stump neuroma», «symptomatic neuroma», «pain neuroma». Relevant articles were included after reading the full text and determining the necessary parameters. The review was prepared in accordance with the recommendations of the “Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines”. onclusions. The results of scientific studies indicate that reinnervation methods (TMR, RPNI, VDMT) are clinically more effective than traditional amputation. These methods can be used with equal effectiveness both for the prevention of late post-amputation complications (symptomatic neuromas, phantom limb pain, residual limb pain) and for their treatment.